Performance Evaluation of Red Pepper Varieties and Types of Seed Bed for The Management of Root Rot (Phytophtora Capsici) Disease at Central Gondar, Northwest, Ethiopia. - Mengist, Yigerm; Birara, Abebe (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Root rot caused by Phytophtora capsici is one of the most important root diseases of pepper. The experiment was conducted at Denbiya and Takusa district with aimed to evaluate effective red pepper varieties and types of seed bed against root rot disease. Five red pepper varieties namely Melka Dera, Melka Oli, Melka Zala, Marco Fana, local; and two seed bed types namely flat and raised bed were used as treatments. Treatments were arranged in a factorial combination in RCBD with three replication. Result showed that the minimum incidence and severity of 28.13 % and 19.8%, respectively was recorded from Melka Oli variety transplanted in a raised bed while the maximum incidence and a severity of 51.03% and 42.8%, respectively were recorded from local red pepper in flat seed bed. The maximum grain yield of 28.81 q/ha and insignificance yield losses were recorded from Melka Oli in raised beds while the minimum grain yield and maximum yield losses 11.12q/ha and 61.44%, respectively were recorded from local red pepper in flat seed bed. Therefore, results suggested that the use of Melka Oli variety transplanted at raised seed bed is promising for significant reduction in root rot incidence and a corresponding increase in yield of red pepper.